2018
DOI: 10.1176/appi.ajp.2017.17050529
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Score for Alzheimer’s Disease: Implications for Memory Performance and Hippocampal Volumes in Early Life

Abstract: Genetic risk for Alzheimer's disease may affect early-life cognition and hippocampal volumes, as shown in two independent samples. These data support previous evidence that some forms of late-life dementia may represent developmental conditions with roots in childhood. This result may vary depending on a sample's genetic risk and may be specific to some types of memory tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
73
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 34 publications
(44 reference statements)
7
73
2
Order By: Relevance
“…Previous work has shown that the clinical AD PRS derived from IGAP summary statistics was predictive of bilateral hippocampal volume in a Brazilian youth cohort [43], aligning with the clinical AD PRS association with left hippocampal volume demonstrated in this study. Together, these results may suggest that genetic drivers of hippocampal volume are influential throughout life.…”
Section: Discussionsupporting
confidence: 89%
“…Previous work has shown that the clinical AD PRS derived from IGAP summary statistics was predictive of bilateral hippocampal volume in a Brazilian youth cohort [43], aligning with the clinical AD PRS association with left hippocampal volume demonstrated in this study. Together, these results may suggest that genetic drivers of hippocampal volume are influential throughout life.…”
Section: Discussionsupporting
confidence: 89%
“…We found no support for the link between AD genetic burden and global, hippocampal. and temporal regions although previous studies have provided evidence for such links during infancy (28,29), childhood (25,30,52,53), and early adulthood (27,(54)(55)(56)(57)(58)(59)(60)(61). The support for such associations does seem stronger in studies during early adulthood than during childhood.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, they report that APOE affects regions that are very different from those reported by Chang and colleagues (30). More recently, Axelrud and colleagues reported that the AD PGRS relates to hippocampal volume in Brazilian children aged 6 to 14 years old (53). However, the source GWAS on which the PGRS in the latter study was based was performed in a population of European ancestry (37).…”
Section: Discussionmentioning
confidence: 94%
“…The genes associated with intelligence are highly expressed in medium spiny neurons of the striatum and pyramidal neurons of the CA1 hippocampus (14), early targets of degeneration in HD and AD respectively, potentially contributing to the severe cognitive decline seen in these diseases. Surprisingly, there is no significant association between the presence of cognitive deficits in HD and genetic risk for AD, though AD PRS predicts memory decline and poorer cognitive performance in healthy children and adults well before the age of risk for AD (39,40). In children, HTT CAG repeat length itself shows a J-shaped relationship with cognition, with maximum cognition at 40-41 repeats (37).…”
Section: Discussionmentioning
confidence: 96%